Імпліцитний складник комунікації в процесі деескалації конфлікту - Передон, Наталія; Peredon, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті здійснено спробу дослідити природу імпліцитності як лінгвістичної категорії, розглянути основні підходи науковців до вивчення цієї проблеми. Автор розмежовує терміни “імпліцитність”, “пропозиція”, “імплікація”, “імплікатура”, уважаючи їх суміжними, але не тотожними поняттями, наводить їх визначення. Окреслено причини, які спонукають мовців до представлення інформації в імпліцитній формі, визначено основні фактори, від яких залежить успішне кодування та декодування повідомлень у процесі комунікації. Імпліцитність схарактеризована як латентно виражена інформація, яка декодується мовцем з опорою на експліцитне значення та обставини й умови комунікації. Автор аналізує специфіку використання повідомлень з імпліцитним складником у процесі деескалації конфлікту. Встановлено, що висловлювання з імпліцитними смислами – частотні в аналізованій ситуації, вони використовуються й ініціатором гармонізації міжособистісної інтеракції, і його об’єктом. Імпліцитно виражена інформація може доповнювати або повністю заміщувати експліцитну. Зважаючи на властиву імпліцитним висловлюванням варіативність декодування, вони можуть сприяти розв’язанню конфлікту або стати причиною його поглиблення. . The focus of this article is to explore the nature of implicitness as a linguistic category. An attempt has been made to consider the basic approaches which exist for dealing with this problem. The author has drawn a distinction between the notions of proposition, implicitness, implication and implicature, considering them to be related, but not identical. The author has described the reasons for which the interlocutors feel impelled to convey their messages implicitly, and has identified the key factors for successfully encoding and decoding information in the process of communication. Implicitness has been described as being linked with latently expressed information, which is then decoded by the interlocutor in accordance with the explicit meaning of a message, and with the circumstances and conditions under which the communication occurs. The author has analyzed specific aspects involved in the use of implicit messages within the process of conflict de-escalation. It has been determined that utterances with implicit meanings are often used in the type of situation which is the object of our analysis, and may be utilized either by the party who is seeking to be the initiator of restored harmonious relations, or by the interlocutor who is the object of the initiative for reconciliation. A point worth noting is that implicitly expressed information can either supplement the explicit messages, or else it can completely replace them. Since it is possible to decode implicit messages in a variety of different ways, they may contribute to the resolution of the conflict, or else, on the contrary, they may actually contribute to its escalation.
Implicitness as a Component of Communication in the Conflict De-escalation Process.
Keywords: імпліцитність; пропозиція; імплікація; імплікатура; декодування; деескалація конфлікту; implicitness; proposition; implication; implicature; decoding; сonflict de-escalation